EFFECTIFITY OF VCT METHOD IN TEACHING SOCIAL SCIENCES TO IMPROVE THE MENTAL ATTITUDE OF MANNERS. (Class Action Research in the VII E Classroom SMPN 4 Bandung) - Febrianti, Puti Laras (International Journal Pedagogy of Social Studies, 2016)
The background of this research of several problems in social sciences studies which tends to strengthen to cognitive aspect, on the other hand the role of teachers is dominantly implemented in the process of studying social sciences, this event tends to be given by delivering speech and discussion without considering the manners of the students. This purpose of the research is to search the Values Clarification Technique Metods and to accomplish the problem of moral and ethics undergone by the students especially the student’s manners during learning the social sciences subject at schools. This research is expected to recognize the effectivity of Values Clarification Technique (VCT) method implementation in improving, selecting and judging the consistent behavior. This class action is released in seventh grade E of SMPN 4 Bandung which has been begun by arranging the Values Clarification Technique (VCT) action plan, and continued by cycle I, cycle II and cycle III. Methode used in this action is called classroom action research (PTK) based on subject of the teacher research on thirty four students. The source is derived from observation, interview, field notes and document. Data analysis is started from collection of data, the interpretation data and the validity of data. The result of research shows that the study of social sciences throug VCT method is able to improve the mental attitude of manners during studying in the classroom. In spite of the difficulties about time, conception and the comprehension of the student on VCT method can be inferred that they tend to perform proper manners of the students. By improving good manner, the active process of study which interpretated by stating, questioning and responds, all will indicate the good attitude and active roles showed by the students in behaving. According to the conclusion above, the VCT method is certainly needed and it should be supported by various materials, models, media, source of studies, and evaluation system. To improve the good manners of the students in studying social sciences, it is exactly necessary to grow moral value and ethics. Teachers are expected to conduct the class research in order to understand, analyze and overcome the problems related to daily taks at school.Keywords: Effectifity, Values Clarification Technique, Social Sciences Learning, attitude of manners